Evaluasi Perataan Laba pada Kinerja Badan Usaha Milik Negara Sebelum dan Setelah Menjadi Perusahaan Terbuka di Indonesia - Prayogo, Bambang; Gunawan, Itjang D. (School of Accountancy, University of Agung Podomoro, 2018)
This study was investigated by using multiple regression analysis method. The sample of this researchis purposive sampling with total 6 years observation. The result of the research shows that SOEsconduct earnings management policy in two years before IPO and two years after IPO by incomeincreasing. In order to get generalized results future research can use all listed state-ownedenterprises until 2016, which is 20 companies with five years-period before and after going public.